Analisa Crack Coil Spring Track Adjuster pada Undercarriage Excavator CAT 320GC - Aldi Lavandida Utama; Santoso, Nugroho; Setyana, Lilik Dwi; Hendaryanto, Ignatius Aris (Jurnal Teknologi dan Rekayasa Alat Berat, 2025)
Heavy equipment, such as excavators, plays a crucial role in infrastructure and mining projects. The demanding worksite conditions and production targets require excavators to maintain high productivity, which can lead to material failures. A critical failure observed in the CAT 320GC excavator was the fracture of the coil spring in the undercarriage system. Several factors can contribute to coil spring failure, including worksite conditions, material defects, inadequate maintenance, and operational errors. This study aims to identify the root causes of coil spring fracture by analyzing its mechanical properties. The research methodology includes chemical composition analysis, visual and microstructural examination, hardness testing, and impact testing. The findings indicate that material failure was primarily caused by corrosion on the surface, which accelerated the fracture process. Additionally, repeated excessive loads from track shoe movements contributed to fatigue failure. The coil spring material was identified as high-carbon steel, closely resembling the 51xx (Chromium Steels) type. The fracture exhibited brittle characteristics with a granular or crystalline pattern, and the average impact energy was measured at 0.1541 J/mm². The coil spring material demonstrated an average hardness of 522.83 VHN, confirming its high hardness but brittle nature. The microstructural analysis revealed a predominance of fine lamellar pearlite in the dark regions of the fractured area.